Religiosity and tax evasion: the application of theory of planned behavior - Ummi Fadhilah (Asian Journal of Islamic Management (AJIM), 2019)
Purpose: This research is aimed to analyze the cheating behavior done by the non-compliance tax payers in Indonesia.Methodology: The data used in this research was primary data from questionnaire which was directly obtained from the object of civil servant working in Batang Regency, Central Java. PLS-SEM was used to test and analyze the data.Findings: The finding showed that there was a negative and significant influence of religiosity to the intention of a civil servant to do tax evasion and there was a positive and significant influence toward people’s intention to do tax evasion.Originality: This paper contributes to the literature by testing the Theory of Planned Behavior to examine noncompliance tax payers